The Effect of HRM Practices on Organizations Financial Performance (OFP) : Case Study on Malaysian Organization - Abdolsaehi, Amir (2013)
Human Resource Management (HRM) practices have been extensive in terms of manufacturing and small and medium enterprises but these theoretical and empirical studies have confined themselves to organizations in the West.Human resource activities are acknowledged to play a prominent role in linking employee capabilities with the firm’s performance requirements but the specific form of this linkage is still debatable This research study is limited to study the effect of HRM practices, technology and organization financial performance. This study provides a view as one of the most significant initiatives in recent years. The implication of this research improved the effect of HRM practices, technology and organization financial performance. In this research, the main objective to examine the effect of HRM practices on OFP, to examine the effect of Technology on HRM towards OFP, to examine the effect of staffing on HRM towards OFP, to examine the effect of develop on HRM towards OFP and to examine the effect of rewards on HRM towards OFP. By doing so, key areas are now offered that practitioners and academics should further explore in order to demonstrate the contribution to the body of knowledge on organization financial performance and to explore in more details which factors are important to organization financial performance to be success.